Poetics in sound art: an interview with Paulo Nenflidio - Yampolschi, Roseane; Mamedes, Clayton Rosa; Nenflidio, Paulo (Revista Vórtex, 2021)
Paulo Nenflidio, in his biographic note, presents himself as an artist who works at the intersection between art, science and technology. A multiple and inventive artist, his works comprise sculptures, installations, objects, instruments and drawings in which sound, electronics, movement, construction, invention, randomness, physics, control, automatons, and workaround come together as elements of artistic expression. Paulo Nenflidio holds a degree in Fine Arts from the School of Communication and Arts of the University of São Paulo and is an electronics technician graduated from the Lauro Gomes Technical School in São Bernardo do Campo. Born in São Bernardo do Campo, the artist maintains his studio in this city. In this interview, we seek to deepen our study about the poetics of Paulo Nenflidio’s works. How his creative trajectory developed, conceptual inspirations that guided the development of his creative processes and his artistic research, as well as the role of sound and silence as forms of poetic expression are issues addressed in this conversation. This interview was conducted by email, between the 20th and 24th of July 2021.